SOSIALISASI SISTEM PENYIMPANAN REKAM MEDIS DI KLINIK PANACEA - Farhansyah, Fani; Nhifvellast, Rhuccy (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Clinics, as healthcare facilities, require organized administration and effective management of medical records to ensure the production of quality information. This community service activity was conducted at Panacea Clinic with the objective of providing counseling to medical record officers on implementing a family folder system for medical record storage. The direct method was employed for this service, involving on-site visits to deliver educational materials and demonstrate proper and accurate medical record storage practices. The outcome of this community service activity was an improvement in the officers' understanding of the family folder storage system. Medical records serve as archives that document all activities within a healthcare facility over a specific period. These records contain information and documents related to patient identity, examinations, treatments, interventions, and other services provided. Medical records play a vital role for both patients and healthcare professionals, necessitating complete and timely record completion by all parties involved.